PENINGKATAN KOMPETENSI GURU PAI - Andi Maidah (BRIGHT VISION Journal of Language and Education, 2022)
This study wants to describe the improvement of PAI teacher competence. Research ii uses a literature study method with data collection techniques from written sources such as books and journals. The results of this study show that in learning interactions PAI teachers are required to be able to build interaction with students because learning interactions are social activities between students and their peers, students and teachers in the form of social communication in class and outside the classroom. Competence is the ability, ability, skill and set of actions carried out responsibly and firmly in carrying out certain tasks. Pedagogic competence means the ability that must be possessed by teachers in mastering everything related to teaching and learning. Personality competence relates to competencies that reflect the attitude or trait of being a good teacher. Professional competence is the ability of each person to carry out duties according to orders and be able to carry out responsibilities properly according to their respective fields. Social competence is an ability related to the way humans live good relationships with each other and also how to socialize appropriately in life.Keywords: Competence, Teacher, PAI